Off-Line Programming Techniques for Multirobot Cooperation System. (2nd July 2013) - Gan, Yahui; Dai, Xianzhong; Li, Dongwei
An off-line programming software designed for multiple robots cooperation system is presented in this paper. At the beginning of the paper, current technologies of robot off-line programming are reviewed and summarized. Then, present status of cooperative functions and cooperative motion instructions defined by predominant robot manufacturers are introduced. Thereafter, principles of robot path planning for cooperative motions are presented. Based on such analysis, software architecture of the off-line programming software designed for general multirobot cooperation system is presented. At last, an off-line programming software with high detailed 3 dimension visualization is achieved. Simulation graphs and snapshots of typical cooperative motions are presented at the end of the paper, which proved the effectiveness of our proposed method.